Psychological Well Being pada Wanita Simpanan - megawati Indri Rabiatul; Ardian Adi Putra; Adri Murni (Psychopolytan : Jurnal Psikologi, 2019)
The purpose of this study is to determine the psychological well-being of mistresses and how to describe women who choose to be mistresses based on Ryff's theory (2010). Participants in this study were two unmarried women at an early age (18-25 to 40 years). This research is qualitative research with a case study approach. The results showed that psychological well-being in low-mistresses through the results of the analysis on six aspects of psychological well-being, namely; self-acceptance, personal growth, life goals, environmental domination, autonomy and positive relationships with others. Mistresses tend not to get improvements in their lives, care too much about the expectations of others, don't think about risks when making decisions. And always look into the past that affects their negative thinking. In this study, it can be explained that those who choose to be mistresses because they have bad experiences in the past and to get happiness from their couple.